Penggunaan Teknologi Informasi, Efektivitas Sistem Informasi Akuntansi, Sistem Pengendalian Intern dan Kinerja Karyawan BPR Kabupaten Gianyar - Manalu, Grace Sarabecca Madaline; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 31 No 2 (2021), 2021)
This study aims to determine the effect of the use of information technology, the effectiveness of accounting information systems, and internal control systems on employee performance. This research was conducted at the Bank Perkreditan Rakyat (BPR) in Gianyar with 140 respondents. Respondent data obtained through a questionnaire, analyzed by multiple linear regressions. The Result Showed That The higher the use of information technologyat the BPR in Gianyar, it can improve employee performance. Keywords: Information Technolog; Information System Effectiveness; Internal Control; Employee Performance.